FOCUS ON TECHNICAL ENTERPRISE RISK MANAGEMENT (2014) - Rivera León, Félix Armando (2015)
Currently the risk levels in business, investment opportunities and personal opportunities; today, they are taking a significant degree within the administration towards the same goals. Our study is figuring out how to build a business strategy, bearing in mind the existence of a set of practices but do not guarantee that the end result will be good, if it serves as a framework to organize the process and make a technical approach feasible.